Preparation method of graphite flake loaded palladium ruthenium platinum hydrogen evolution catalyst

The preparation method of palladium-ruthenium-platinum catalyst supported on graphite sheets solves the problems of complex preparation and high cost of existing platinum-based catalysts, and achieves improved hydrogen evolution performance with low platinum addition, which is suitable for the field of electrolytic hydrogen production.

CN120945432APending Publication Date: 2025-11-14HEBEI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510919869.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

The preparation process of existing platinum-based hydrogen evolution catalysts is complex, costly, and their performance needs to be improved. The limited amount of platinum used also hinders their widespread application in the field of electrolytic hydrogen production.

Method used

A method for preparing a graphite-supported palladium-ruthenium-platinum catalyst was developed. The catalyst with low platinum content was prepared through a two-step process of high-temperature calcination and hydrothermal reaction. The process involves mixing ruthenium oxide and palladium oxide with graphite and then reacting the mixture with chloroplatinic acid solution to form a graphite-supported palladium-ruthenium-platinum catalyst.

Benefits of technology

The prepared catalyst exhibits excellent hydrogen evolution performance at high current density, with an overpotential lower than that of commercial Pt/C catalysts, and is inexpensive, making it commercially viable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120945432A_ABST
    Figure CN120945432A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphite flake loaded palladium ruthenium platinum hydrogen evolution catalyst. The preparation method comprises the following steps: weighing ruthenium oxide trihydrate and anhydrous palladium oxide according to a molar ratio of Ru to Pd of (10-5): 1, mixing, grinding, adding a certain amount of graphite, fully grinding, pressing into a small wafer, calcining the small wafer in a muffle furnace in an air atmosphere at 500-800 DEG C for 1-3 hours to obtain a precursor A, transferring a certain amount of the precursor A into an H2PtCl6 solution, and carrying out vacuum drying to obtain the catalyst. The preparation method comprises the following steps: adding palladium, ruthenium and platinum into a reaction kettle to form a turbid liquid, heating the obtained turbid liquid in a closed reaction kettle at 160-200 DEG C for 5-10 hours to complete a hydrothermal process, and carrying out suction filtration and drying to obtain the graphite flake supported palladium, ruthenium and platinum hydrogen evolution catalyst. The prepared catalyst is used for catalytic hydrogen production, the hydrogen evolution overpotential under the current density of-50 mA cm <-2 > is low, the excellent hydrogen evolution catalytic property is shown, and the potential commercial application prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a catalyst, particularly a method for preparing a graphite sheet-supported palladium-ruthenium-platinum hydrogen evolution catalyst, belonging to the field of catalytic materials technology. Background Technology

[0002] Hydrogen is considered one of the ideal clean energy sources due to its high energy density and zero carbon emissions. In industry, hydrogen production is mainly achieved through the synthesis of fossil fuels such as natural gas reforming and coal gasification. Currently, with the rapid development of wind and solar power, the gradual reduction of electricity prices has become an inevitable trend. Against this backdrop, water electrolysis for hydrogen production is gradually becoming the preferred method due to its simple operation and environmental friendliness. Hydrogen production through water electrolysis is achieved through a highly efficient hydrogen evolution reaction (HER). Catalysts are crucial for reducing energy consumption during the electrolysis process, which is essential for the commercial production of hydrogen. Specifically, HER catalysts reduce the hydrogen evolution overpotential, thereby significantly reducing the cell voltage and energy consumption. Developing novel HER catalysts has become a focus of industry attention. Research shows that platinum, with its lowest HER overpotential and fast HER kinetics, is considered a good HER catalyst and has seen some application in commercial hydrogen electrolysis. However, the limited reserves and high price of platinum severely hinder its widespread application in practical hydrogen electrolysis. Therefore, developing platinum-based binary and even ternary hydrogen evolution catalysts has become a research hotspot in the hydrogen energy field, aiming to reduce platinum usage while maintaining high catalytic activity for hydrogen evolution, ultimately achieving economical and efficient hydrogen production. In existing technologies, novel hydrogen evolution catalysts can be prepared by reducing the amount of Pt through metal doping. For example, Yu Jing et al. (CN118854365A) prepared a platinum-ruthenium hydrogen evolution catalyst using ruthenium trichloride and chloroplatinic acid hexahydrate as raw materials. Gan Tuanjie et al. (CN114381743A) prepared a nitrogen-doped carbon nanotube-supported CuPtNi alloy nanoparticle composite hydrogen evolution catalyst, which to some extent solved the problem of unstable performance of composite hydrogen evolution catalysts. Li et al. developed a carbon nanosheet-supported palladium-ruthenium-platinum hydrogen evolution catalyst using palladium chloride, chloroplatinic acid hexahydrate, and ruthenium chloride trihydrate as raw materials, employing chemical reduction and heating hydrolysis methods. The above technologies generally suffer from drawbacks such as complex preparation processes and high costs. In addition, the performance of the catalysts needs to be further improved. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing a graphite-supported palladium-ruthenium-platinum hydrogen evolution catalyst. The preparation process is simple, requires a low amount of platinum, and improves the catalyst's catalytic performance.

[0004] The concept of this invention is as follows: First, ruthenium oxide hydrate (RuO2·3H2O) with an amorphous structure and anhydrous palladium oxide (PdO) are mixed, ground, and then mixed with graphite. The mixture is then calcined at high temperature to prepare a precursor. Subsequently, the obtained precursor is mixed with chloroplatinic acid solution and hydrothermally heated at a certain temperature for a period of time to finally obtain a graphite sheet-supported palladium-ruthenium-platinum hydrogen evolution catalyst.

[0005] Specifically, the preparation method of the present invention includes the following steps: (1) Material preparation Materials required: Ruthenium oxide trihydrate (RuO2·3H2O), anhydrous palladium oxide (PdO), chloroplatinic acid hexahydrate (H2PtCl6·6H2O), graphite; (2) Catalyst preparation Step 1: High-temperature calcination to prepare precursor A Ruthenium trihydrate and anhydrous palladium oxide were mixed in a mortar, with the molar ratio of Ru to Pd being (10~5):1. The mixture was ground for 5~12 min, and then graphite was added, with the mass ratio of graphite to anhydrous palladium oxide being (20~10):1. The mixture was ground for another 5 min. The mixture was then pressed into discs with a thickness of 1 mm and a diameter of 12 mm using a tablet press. The discs were then transferred to a muffle furnace and calcined in an air atmosphere at 500~800℃ for 1~3 h to obtain precursor A. Step 2: Hydrothermal reaction Precursor A was weighed and placed in a centrifuge tube. A solution of H2PtCl6 with a concentration of 0.5~2.5 mg mL⁻¹ was added, and the mixture was sonicated for 15~30 min to form a suspension. The suspension was then transferred to a high-pressure reactor, sealed, and heated at 160~200℃ for 5~10 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered. The resulting black filter residue was dried in air at 80℃ for 6 h to obtain a black powder. This black powder is the final graphite sheet-supported palladium-ruthenium-platinum hydrogen evolution catalyst, denoted as PdxRuy-Pt / GS, where GS is the abbreviation for graphite sheet.

[0006] The following are preferred conditions for the preparation method described in this invention: In the preparation method described above, when ruthenium trihydrate oxide (RuO2·3H2O) and anhydrous palladium oxide (PdO) are mixed, the molar ratio of ruthenium to palladium is 5.6:1.

[0007] The preparation method involves calcining at 650°C in an air atmosphere in a muffle furnace for 1 hour.

[0008] In the preparation method described above, the concentration of the H2PtCl6 solution is 0.5 mg mL⁻¹.

[0009] In the preparation method described above, the hydrothermal reaction temperature is 175°C.

[0010] (3) Preparation of working electrode and catalytic performance test of hydrogen evolution catalyst Materials required for catalyst performance testing: glassy carbon electrode, graphite rod, Hg / HgO reference electrode, and 1 mol L⁻¹ KOH solution.

[0011] Two mg of PdxRuy-Pt / GS catalyst was dissolved in 0.5 mL of Nafion solution and sonicated for 30 min to obtain a suspension. Then, 10 μL of this suspension was pipetted onto a glassy carbon electrode and allowed to air dry, thus preparing a glassy carbon electrode coated with the hydrogen evolution catalyst. Subsequently, this electrode was used as the working electrode, a graphite rod as the counter electrode, Hg / HgO as the reference electrode, and 1 mol L⁻¹ KOH as the electrolyte to construct a classic three-electrode system. The hydrogen evolution catalytic performance was tested using a CHI 660B electrochemical workstation. During linear sweep voltammetry (LSV), the scan rate was set to 5 mV s⁻¹, and the potential range was set to -0.2 V to -1.1 V to obtain the hydrogen evolution curve. Next, the voltage corresponding to a current density of -10 mA cm⁻² in the hydrogen evolution curve was selected as the center. A voltage range of ±50 mV from this center was chosen as the selected voltage range, and the corresponding current was used as the selected current to plot a Tafel curve. The voltage values ​​during this period were corrected according to the formula: Reversible hydrogen electrode potential = Measured electrode potential + 0.0592pH + 0.098 V, resulting in the final linear sweep voltammetry (LSV) curve and Tafel curve. The chronoamperometry (CA) test curve is the relationship between time and current recorded at the voltage (vs. Hg / HgO) corresponding to a current density of -10 mA cm⁻² in the LSV curve.

[0012] The beneficial effects of this invention are as follows: This invention prepares a graphite-supported palladium-ruthenium-platinum hydrogen evolution catalyst via a two-step method of high-temperature calcination and hydrothermal reaction. This catalyst exhibits a hydrogen evolution overpotential of 70 mV at a current density of -50 mA cm⁻², significantly lower than the 85 mV of commercial Pt / C catalysts, demonstrating superior hydrogen evolution performance. This invention features a simple preparation process, low cost, and improved catalytic performance, making it commercially viable. Attached Figure Description

[0013] Figure 1 The image shows the XRD pattern of the catalyst prepared in Example 1.

[0014] Figure 2 This is a SEM image of the catalyst prepared in Example 1.

[0015] Figure 3 The LSV curve of the hydrogen evolution reaction of the catalyst prepared in Example 1 in 1 mol L⁻¹ KOH solution is shown.

[0016] Figure 4 The image shows the Tafel curve of the catalyst prepared in Example 1.

[0017] Figure 5 The image shows the CA test result of the catalyst prepared in Example 1. Detailed Implementation

[0018] The following examples are used to illustrate the present invention. Example 1

[0019] (1) Material preparation Materials required for catalyst preparation: ruthenium oxide trihydrate (RuO2·3H2O), anhydrous palladium oxide (PdO), chloroplatinic acid hexahydrate (H2PtCl6·6H2O), graphite; Materials required for catalyst performance testing: glassy carbon electrode, graphite rod, Hg / HgO reference electrode, and 1 mol L⁻¹ KOH solution.

[0020] (2) Preparation process Weigh 40 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 5 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 10 minutes. Then add 0.1 g of graphite and continue grinding for 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 650°C for 1 hour to obtain precursor A.

[0021] 10 mg of precursor A was weighed and placed in a 10 mL centrifuge tube. Then, 10 mL of a 0.5 mg mL⁻¹ H₂PtCl₆ solution was added, and the mixture was sonicated for 25 min to form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 175 °C for 8 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder. This black powder is the final graphite-supported palladium-ruthenium-platinum hydrogen evolution catalyst, PdxRuy-Pt / GS.

[0022] (3) Test of catalyst hydrogen evolution performance The hydrogen evolution performance of the prepared catalyst was tested using the following method: Materials required for catalyst performance testing: glassy carbon electrode, graphite rod, Hg / HgO reference electrode, and 1 mol L⁻¹ KOH solution.

[0023] Two mg of the catalyst prepared above was dissolved in 0.5 mL of Nafion solution and sonicated for 30 min to obtain a suspension. Then, 10 μL of this suspension was pipetted onto a glassy carbon electrode and allowed to air dry, thus preparing a glassy carbon electrode coated with the catalyst. This electrode was used as the working electrode, a graphite rod as the counter electrode, Hg / HgO as the reference electrode, and 1 mol L⁻¹ KOH as the electrolyte to construct a classic three-electrode system. The hydrogen evolution performance of the prepared catalyst was tested using a CHI 660B electrochemical workstation. Linear sweep voltammetry (LSV) was performed with a scan rate set to 5 mV s⁻¹ and a potential range of -0.2 V to -1.1 V to obtain the LSV curve of the hydrogen evolution reaction. To compare the hydrogen evolution performance with that of the Pt / C catalyst, the Pt / C catalyst was also subjected to the same tests, and the results are as follows: Figure 3 As shown. Next, the voltage corresponding to a current density of -10 mA cm⁻² in the LSV curve was selected as the center. The voltage range within ±50 mV of this center was used as the selected voltage range, and the corresponding current was used as the selected current to plot the Tafel curve. The voltage values ​​were corrected according to the formula: Reversible hydrogen electrode electrode potential = Measured electrode potential + 0.0592pH + 0.098 V, resulting in the final Tafel curve, as shown. Figure 4 As shown.

[0024] Figure 1The XRD pattern of the prepared catalyst PdxRuy-Pt / GS is shown, along with standard cards for PdO, elemental Pd, RuO2, and elemental Pt. A distinct broad peak appears at approximately 26.1° 2θ, corresponding to the (002) crystal plane of graphite, indicating the presence of graphite in the catalyst. The diffraction peaks at 28.1°, 35.1°, 54.4°, and 58.1° 2θ in the figure correspond to the (110), (101), (211), and (220) crystal planes of tetragonal RuO2 (JCPDS, NO. 21-1172), indicating the presence of RuO2 in the catalyst. The two small diffraction peaks at 33.9° and 71.5° in the spectrum correspond to the (101) and (211) crystal planes of PdO (JCPDS, NO. 43-1024), respectively, indicating that the catalyst retains a small amount of PdO after calcination and hydrothermal treatment. It is worth noting that the diffraction peaks at 2θ of 40.1°, 46.7°, and 68.1° coincide with the (111), (200), and (220) crystal planes of face-centered cubic palladium (JCPDS, NO. 5-681), respectively, indicating the presence of elemental palladium in the catalyst. Furthermore, the diffraction peaks at 39.8°, 46.2°, 67.5°, and 81.3° in the spectrum correspond to the (111), (200), (220), and (311) crystal planes of cubic Pt (JCPDS, NO. 4-802), respectively, indicating that after calcination and hydrothermal treatment, some chloroplatinic acid has been reduced to elemental Pt. Therefore, the main components of the catalyst prepared in this invention are graphite, PdO, elemental Pd, RuO2, and elemental Pt. A literature review revealed no reports of studies on the preparation of hydrogen evolution catalysts containing the above-mentioned substances using calcination and hydrothermal methods.

[0025] Figure 2 These are SEM images of the prepared catalyst at different scales. From the SEM image (a) with a scale bar of 2 μm, it can be seen that the surface of the prepared material is uneven, composed of a large number of accumulated particles, and exists in a blocky form. Close observation reveals many pores on the surface, indicating that the surface of the prepared catalyst is relatively porous. From the SEM image (a1) with a scale bar of 200 nm, it can be seen that the catalyst contains many irregular blocky particles with a diameter of approximately 50 nm, and these particles are all attached to the flake graphite. Therefore, the prepared catalyst is a graphite sheet-supported catalyst. Literature review shows that this type of porous, loose, and flake-shaped hydrogen evolution catalyst has not yet been reported.

[0026] Figure 3 The image shows the LSV curve of the hydrogen evolution reaction of the prepared catalyst in 1 mol L⁻¹ KOH solution. Figure 3As can be seen, when the current density reaches -10 mA cm⁻², the overpotentials required for HER to occur by the prepared catalyst and Pt / C are -25.95 mV and -25.06 mV, respectively, which are not significantly different. However, when the current density reaches -50 mA cm⁻², the overpotentials of the two catalysts reach -70 mV and -85 mV, respectively. This means that the catalyst prepared using this patent can reduce the overpotential by 15 mV compared to the commercial Pt / C electrode. Therefore, under high current density conditions, the HER electrocatalytic performance of the PdxRuy-Pt / GS catalyst is superior to that of the commercial Pt / C catalyst.

[0027] Figure 4 This is a Tafel curve of the prepared catalyst. Figure 4 The Tafel curve slope of PdxRuy-Pt / GS is approximately -53.64 mV dec⁻¹, which is very close to the -52.86 mV dec⁻¹ slope of the commercial catalyst Pt / C. This indicates that PdxRuy-Pt / GS exhibits excellent hydrogen evolution reaction kinetics.

[0028] Figure 5 The chronoamperometry curves show the potential values ​​(vs. Hg / HgO) of the prepared catalyst PdxRuy-Pt / GS at a current density of -10 mA cm⁻², i.e., -0.96 V. After 4 hours of polarization, the hydrogen evolution current density on the electrode decreased from -5.73 to -4.84 mA cm⁻², with a retention rate of 84%. This indicates that the prepared hydrogen evolution catalyst has excellent long-term durability. Example 2

[0029] Weigh 40 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 5 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 10 minutes. Then add 0.1 g of graphite and continue grinding for 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 550°C for 1 h to obtain precursor A.

[0030] 5 mg of precursor A was weighed and placed in a 10 mL centrifuge tube. Then, 10 mL of a 0.8 mg mL⁻¹ H₂PtCl₆ solution was added, and the mixture was sonicated for 25 min to form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 190 °C for 10 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder, which is the prepared catalyst.

[0031] The hydrogen evolution performance of the catalyst was tested on a CHI 660B electrochemical workstation according to the method in Example 1. LSV curves showed that the overpotential required for HER was -80.78 mV when the current density reached -50 mA cm⁻². Tafel curves showed that the Tafel slope of the prepared catalyst was -65.78 mV dec⁻¹. All these performance indicators are superior to those of commercial Pt / C. In CA testing, the catalyst maintained 69% of its hydrogen evolution current density after 4 hours, demonstrating excellent long-term durability. Example 3

[0032] Weigh 10 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 5 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 6 minutes. Then add 0.1 g of graphite and continue grinding for 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 800°C for 2 hours to obtain precursor A.

[0033] 15 mg of precursor A was weighed into a 10 mL centrifuge tube, followed by the addition of 10 mL of a 0.5 mg mL⁻¹ H₂PtCl₆ solution. The mixture was sonicated for 30 min to ensure thorough mixing and form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 185 °C for 6 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder, which was the prepared catalyst.

[0034] Hydrogen evolution performance was tested on a CHI 660B electrochemical workstation according to the method in Example 1. LSV curves showed an overpotential of -77.78 mV at a current density of -50 mA cm⁻². Tafel curves showed a Tafel slope of -65.78 mV dec⁻¹ for the prepared catalyst. These performance indicators are all superior to those of commercial Pt / C. In CA testing, the catalyst maintained 71% of its hydrogen evolution current density after 4 hours, demonstrating excellent long-term durability. Example 4

[0035] Weigh 50 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 10 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 10 minutes. Then add 0.1 g of graphite and continue grinding for 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 550°C for 3 hours to obtain precursor A.

[0036] 8 mg of precursor A was weighed into a 10 mL centrifuge tube, followed by the addition of 6 mL of a 1.0 mg mL⁻¹ H₂PtCl₆ solution. The mixture was sonicated for 20 min to ensure thorough mixing and form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 195 °C for 8 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder, which was the prepared catalyst.

[0037] Hydrogen evolution performance was tested on a CHI 660B electrochemical workstation according to the method in Example 1. LSV curves showed an overpotential of -75.36 mV at a current density of -50 mA cm⁻². Tafel curves showed a Tafel slope of -71.08 mV dec⁻¹ for the prepared catalyst. These performance indicators are all superior to those of commercial Pt / C. In CA testing, the catalyst maintained 76% of its hydrogen evolution current density after 4 hours, demonstrating excellent long-term durability. Example 5

[0038] Weigh 35 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 5 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 5 minutes. Then add 0.1 g of graphite and continue grinding for another 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 700°C for 1 h to obtain precursor A.

[0039] 12 mg of precursor A was weighed into a 10 mL centrifuge tube, followed by the addition of 12 mL of a 1.5 mg mL⁻¹ H₂PtCl₆ solution. The mixture was sonicated for 30 min to ensure thorough mixing and form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 165 °C for 7 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder, which was the prepared catalyst.

[0040] Hydrogen evolution performance was tested on a CHI 660B electrochemical workstation according to the method in Example 1. The LSV curve showed an overpotential of -74.08 mV at a current density of -50 mA cm⁻². The Tafel curve showed a Tafel slope of -56.11 mV dec⁻¹ for the prepared catalyst. All these performance indicators are superior to those of commercial Pt / C. In the CA test, the catalyst maintained 53% of its hydrogen evolution current density after 4 hours, demonstrating excellent long-term durability. Example 6

[0041] Weigh 80 mg of ruthenium oxide trihydrate (RuO2·3H2O) and 10 mg of anhydrous palladium oxide (PdO) and grind them thoroughly in a mortar for 6 minutes. Then add 0.1 g of graphite and continue grinding for 5 minutes. After that, press the mixture into sheets. Then, transfer the pressed sheets to a muffle furnace and calcine them in air at 600°C for 3 hours to obtain precursor A.

[0042] 18 mg of precursor A was weighed into a 10 mL centrifuge tube, followed by the addition of 5 mL of a 2.5 mg mL⁻¹ H₂PtCl₆ solution. The mixture was sonicated for 25 min to ensure thorough mixing and form a suspension. The suspension was then transferred to a high-pressure reactor, sealed tightly, and heated at 195 °C for 9 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80 °C for 6 h to obtain a black powder, which was the prepared catalyst.

[0043] Subsequently, hydrogen evolution performance was tested on a CHI 660B electrochemical workstation according to the method in Example 1. The LSV curve showed an overpotential of -87.38 mV at a current density of -50 mA cm⁻². The Tafel curve showed a Tafel slope of -47.90 mV dec⁻¹ for the prepared catalyst. All these performance indicators are superior to those of commercial Pt / C. In the CA test, the catalyst maintained 69% of its hydrogen evolution current density after 4 hours, demonstrating excellent long-term durability.

Claims

1. A method for preparing a graphite sheet-supported palladium-ruthenium-platinum hydrogen evolution catalyst, characterized in that, Includes the following steps: (1) Material preparation Materials required: Ruthenium oxide trihydrate, anhydrous palladium oxide, chloroplatinic acid hexahydrate, graphite; (2) Catalyst preparation Step 1: High-temperature calcination to prepare precursor A Ruthenium trihydrate and anhydrous palladium oxide were mixed in a mortar, with the molar ratio of Ru to Pd being (10~5):

1. The mixture was ground for 5~12 min, and then graphite was added, with the mass ratio of graphite to anhydrous palladium oxide being (20~10):

1. The mixture was ground for another 5 min. The mixture was then pressed into discs with a thickness of 1 mm and a diameter of 12 mm using a tablet press. The discs were then transferred to a muffle furnace and calcined in an air atmosphere at 500~800℃ for 1~3 h to obtain precursor A. Step 2: Hydrothermal reaction Weigh precursor A and place it in a centrifuge tube. Add an amount of 0.5–2.5 mg / mL of the solution. -1 The H2PtCl6 solution was sonicated for 15-30 min to form a suspension. The suspension was then transferred to a high-pressure reactor, sealed, and heated at 160-200℃ for 5-10 h to complete the hydrothermal reaction. After cooling to room temperature, the mixture was filtered, and the resulting black filter residue was dried in air at 80℃ for 6 h to obtain a black powder, thus obtaining the graphite-supported palladium-ruthenium-platinum hydrogen evolution catalyst.

2. The preparation method according to claim 1, characterized in that, The molar ratio of Ru to Pd is 5.6:

1.

3. The preparation method according to claim 1, characterized in that, The calcination temperature in the muffle furnace under air atmosphere was 650℃, and the calcination time was 1 h.

4. The preparation method according to claim 1, characterized in that, The concentration of the H2PtCl6 solution is 0.5 mg / mL. -1 .

5. The preparation method according to claim 1, characterized in that, The hydrothermal reaction temperature is 175℃.

6. The preparation method according to claim 1, characterized in that, The hydrothermal reaction time was 8 hours.

Citation Information

Patent Citations

  • Composite hydrogen evolution catalyst as well as preparation method and application thereof

    CN114381743A

  • Preparation method, product and application of platinum-ruthenium alloy electrolytic water / seawater hydrogen evolution catalyst

    CN118854365A